MEASURES OF CRIMINAL PROCEDURAL COERCION (Conferencea, 2022)
According to Article 13 of the Constitution of the Republic of Uzbekistan, democracy in the Republic of Uzbekistan is based on universal principles, according to which a person, his life, his freedom, his dignity and other inalienable rights are recognized as the highest value. The direct protection of democratic rights and freedoms by the c and laws is the constitutional and legal basis for the application of coercive measures of criminal procedure